La Guerra de Malvinas en primera persona: Museo Miguel Ángel Boezzio (1998) de Federico León - Ricardo Dubatti (Nuevo mundo - Mundos Nuevos, 2019)
The Malvinas War (1982) marks a before and after in the history of Argentina. 37 years after the war, formulating an organic historical reading is conflicting because –in keeping with the concepts of Agamben– it has never stopped happening. The theater is positioned in the post-war Argentina as a memorialist construct, a valuable territory due to its potential to activate the works of memory. The case of the Museo Miguel Ángel Boezzio (1998) by Federico León (Buenos Aires, 1975), occupies a central space in our research. This is because it articulates theater, testimony, conference and museum from a critical perspective to build a particular representation of the war and its effects. The present article seeks to examine from the guidelines of Comparative Poetics in what ways Leon produces a stimulus device that aims to mobilize the viewer and allows not only revisit facts from the recent past, but also produce new thoughts about history.